Sumbangan Kaligrafi Arab dalam Kesenian Islam: Suatu Kajian Sejarah - Hj. Abdullah, Mohd. Bakhir (Jurnal Usuluddin, 2007)
The combination of calligraphy and art is an association that leads to the beauty of Islam. The Qur'an which is decorated with calligraphic writing or Arabic calligraphy reflects the beauty of the Islamic religion itself. This beauty differentiates it from calligraphies of other languages. The patterns of letters that connect with each other express the beauty of Arabic calligraphy. The revelation of the Qur'an in the Arabic language and script as a medium between the Word of Allah with His creatures proves to mankind of how beautiful the Arabic calligraphy is; thus it was chosen by Allah the All-Mighty. Arabic calligraphy also possesses high esthetical value when it is decorated with the various calligraphic patterns such as Dewan, Kufi, Nashk, Rikaah, Thulus and others. Indeed, the uniqueness of these calligraphic patterns induce men to further create new ones and also influences the soul towards peace, happiness, prosperity and at the same time, urges mankind towards the Divine Truth.